2020
DOI: 10.3390/biom10091211
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin’s Impact on Antioxidative and Anti-Inflammatory Reprogramming in Homeostasis and Disease

Abstract: There is a growing consensus that the antioxidant and anti-inflammatory properties of melatonin are of great importance in preserving the body functions and homeostasis, with great impact in the peripartum period and adult life. Melatonin promotes adaptation through allostasis and stands out as an endogenous, dietary, and therapeutic molecule with important health benefits. The anti-inflammatory and antioxidant effects of melatonin are intertwined and are exerted throughout pregnancy and later during developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(152 citation statements)
references
References 222 publications
(267 reference statements)
1
139
0
12
Order By: Relevance
“…Therefore, improved chemotherapeutic agents that display little to no unfavorable off-target effects need to be identified. Melatonin is a natural hormone that does not display toxicity and regulates numerous physiological processes, including the circadian rhythm and antioxidative processes (63,64). An increasing number of studies have demonstrated that melatonin also possesses anticancer properties in several types of cancer (65,66), for example, melatonin inhibits proliferation and invasion via repression of miRNA-155 in glioma cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improved chemotherapeutic agents that display little to no unfavorable off-target effects need to be identified. Melatonin is a natural hormone that does not display toxicity and regulates numerous physiological processes, including the circadian rhythm and antioxidative processes (63,64). An increasing number of studies have demonstrated that melatonin also possesses anticancer properties in several types of cancer (65,66), for example, melatonin inhibits proliferation and invasion via repression of miRNA-155 in glioma cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this more generalized theoretical approach, our group has demonstrated here the expected neurological impact of shared pathobiology between AIS and COVID-19 here, and the debilitating condition that characterizes PCNS ( 150 ) manifests as chronic fatigue, impaired thinking, depression, anxiety, breathing difficulties, and muscle weakness ( 40 , 40 , 149 , 150 ). Thus, we suggest that treatment with known Food and Drug Administration (FDA)-approved immunomodulatory hormones such as melatonin ( 14 , 15 , 33 , 156 162 ) and nutraceuticals such as curcumin ( 163 ) might be expected to enhance the likelihood of PCNS patients benefitting from any neurorehabilitation interventions as a matter of priority.…”
Section: Covid Neurological Manifestations and Implications For Neurmentioning
confidence: 99%
“…By regulating the circadian rhythm and thereby reducing chronodisruption, fewer oxidative reagents are generated [ 69 ]. Its antioxidant functions have been reviewed extensively [ 69 , 90 ]. Because its first, second and third tier metabolites retain their scavenger function, melatonin induces an antioxidant cascade that quenches ten radical products, which makes it more efficient than glutathione [ 69 , 90 ].…”
Section: Human Milk Antioxidantsmentioning
confidence: 99%